Effects of TASC Learning Model (Thinking Actively In A Social Context) on Ability Problem-solving in Natural Resource Management Materials - Mutaqy, Rosikh Musabikha; Nasution, Nasution; Purnomo, Nugroho Hari (The Indonesian Journal of Social Studies, 2019)
This study aims to analyze the effect of the TASC learning model on students' ability to solve problems in natural resource management material. This study uses an experimental method with the design of Non-equivalent Pretest-Postest Control Group Design. The results of this study indicate that the TASC learning model has an effect on students' problem solving abilities in natural resource management materials, where experimental class students who use the TASC learning model have better problem solving skills than the control class that uses the class discussion model. in natural resource management material. Based on the results of hypothesis testing, it was concluded that there were significant differences between students learning using the TASC learning model (Active Thinking in Social Context) with students learning to use cooperative type class discussion learning models to solve problems.